GENDER FEATURES OF ADAPTATION OF SUBJECTS TO THE SITUATION OF CHANGE OF TYPES OF PROFESSIONAL ACTIVITIES - Fomina Е.А.; Solomonov , V.A. (Modern Psychology, 2021)
The features of adaptation of subjects to the situation of changing types of professional activity, taking into account their gender, are considered. The study involved 292 people, including 146 men, 146 women, who in one form or another change their professional activities (undergoing training in various programs, un- employed, looking for a new vacancy). Empirical material was collected using computer testing, standardized psychological methods were used. In men, connections have been established between all components of adaptability, resilience and coping strategies; the key predictor is “engagement”. For men, cognitive coping strategies are not productive. The respondents from the female sample did not reveal significant correlations between “moral normativity” as a factor of adaptability, components of resilience and coping strategies, the key factor being “risk taking”. Women tend to use cognitive and emotional coping strategies. It was revealed that the ability to adapt to the situation of changing types of professional activity in all subjects is associated with the readiness to accept changes in life ("adaptive abilities"); with the desire to get involved in activities that you can enjoy ("involvement"); with an openness to new experience ("risk taking").